RESPON SISWA TERHADAP MEDIA PEMBELAJARAN KOMIK PADA MATERI EKOLOGI DI KELAS X SMA - Lijana, Lijana; Putri Panjaitan, Ruqiah Ganda; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis research aimed to know the response of students to comic learning media on ecology material in class X SMA. The research method apply in this research is descriptive research. The descriptive research used in this research is the survey. The sampling technique used is purposive sampling. The subject of this study is 130 students of grade X SMA from four senior high schools in Pontianak. The research instrument used is a closed questionnaire. The student response questionnaire consists of 2 aspects, namely the response and reaction aspects. The criteria of response consists of five indicators are format, relevance, interest, satisfaction, and confident. This research is done by giving comic learning mediaÂ followed by giving response questionnaire to the students. The analysis of the questionnaire shows that the average value of student response on the response aspect is 73.4% while the reaction aspect is 74.4%. %. It can be concluded that the average percentage of student response is 73,9% and categorized strong.Â Keywords: Ecological material, comic learning media, student response.